Pathways Toward Inclusive Livestock Carbon Markets in Africa - Jain, K.; Dokka, D.; Crane, Todd A. (International Livestock Research Institute, 2025)
In recent years, we have seen a rapid increase of voluntary carbon markets in African livestock sectors, as well as an increasing amount of biophysical research on the potential for carbon sequestration and GHG emission avoidance. This policy brief outlines socio-economic and institutional barriers to scaling inclusive livestock-focused carbon finance across Africa. and makes practical research recommendations to address these barriers. Analysing interviews with stakeholders from over 30 organizations—including NGOs, development agencies, local farmer cooperatives, carbon project developers, and research institutes— as well as grey literature on carbon methodologies, the objective is to inform targeted policy and programmatic responses that can unlock carbon revenue streams for smallholder and pastoralist communities, while ensuring environmental integrity and equitable benefit-sharing. The brief outlines the current state of livestock carbon markets, identifies key challenges and offers practical recommendations to enable inclusive participation